Menyingkap Tabir Masa Lalu: Sejarah Berdirinya Dewan Kesenian Makassar - Limola, Fajar Sidiq; Anjarsari, Hilda (CV. Social Politic Genius (SIGn), 2023)
This study aims to document the establishment process and role of the Makassar Arts Council. This study uses a qualitative content analysis. This analysis enables researchers to construct a coherent and comprehensive historical narrative, and ultimately yields a conclusion. The results show that DKM was established in response to the challenging and conflict-ridden dynamics of the arts in Makassar, especially concerning the politicization of the arts. This situation prompted artists to form a more neutral venue to encourage artistic expression free from political intimidation, which ultimately crystallized in the establishment of DKM on July 25, 1969. Since then, DKM has grown into an institution that continuously supports and nurtures the arts, making Makassar a center for dynamic and sustainable artistic activities. Therefore, it is recommended that historians thoroughly document the historical phases of DKM in the social and political context to enrich the archives of Indonesian art history. Meanwhile, artists are encouraged to actively collaborate with DKM in creating innovative works and promoting their works more broadly. The Makassar Municipal Government is recommended to enhance financial support and infrastructure for DKM, making it a strategic partner in developing cultural policies. Lastly, the general public is encouraged to become more involved in DKM activities, supporting artistic initiatives that can enrich local cultural life and ensure the sustainability and dynamic growth of the arts in Makassar.